Inheritance of a Balanced t(12;20)(q24.33;p12.2) and Unbalanced der(13)t(7;13)(p21.3;q33.2) from a Maternally Derived Double Balanced Translocation Carrier - Peterson, Jess F.; Geddes, Gabrielle C.; Basel, Donald G.; Schippman, Dana; Grignon, John W., Jr.; vanTuinen, Peter; Kappes, Ulrike P. (Journal of Pediatric Genetics, 2018)
We report a 4-month-old male proband with a history of prominent forehead, hypertelorism, ear abnormalities, micrognathia, hypospadias, and multiple cardiac abnormalities. Initial microarray analysis detected a concurrent 7p21.3-p22.3 duplication and 13q33.2-q34 deletion indicating an unbalanced rearrangement. However, subsequent conventional cytogenetic studies only revealed what appeared to be a balanced t(12;20)(q24.33;p12.2). Fluorescence in situ hybridization (FISH) using chromosome-specific subtelomere probes confirmed the presence of an unbalanced der(13)t(7;13)(p21.3;q33.2) and balanced t(12;20)(q24.33;p12.2), both of maternal origin. In addition to our unique clinical findings, this case highlights the benefits and limitations of both conventional cytogenetic studies and microarray analysis and how FISH complements each methodology.
Keywords: 7p21.3-p22.3 duplication; 13q33.2-q34 deletion; unbalanced translocation; double balanced translocation carrier; fluorescence in situ hybridization; array comparative genomic hybridization